A case of late presenting chronic granulomatous disease - Yalçın, Işık; Güler, Nermin; Öneş, Ülker; Salman, Nuran; Anak, Sema (The Turkish Journal of Pediatrics, 1990)
An eleven-year-old boy with a history of severe lung infection which had been resistant to antibiotic therapy for a period of six months demonstrated a functional leukocyte defect similar to that found in children with chronic granulomatous disease (CGD). X-ray findings suggested a hilar mass, and granulomatous lesions developed on the thorax wall. The documentation of this case suggests that there may be a late presenting form of CGD.
Keywords: chronic granulomatous disease; late onset